PROPOSED IMPROVEMENT OF FAJAR DAILY NEWSPAPER PRODUCTS WITH A SIX SIGMA APPROACH - Nadzirah Ikasari Syamsul; Kifayah Amar; Syamsul Bahri; Mario Alif Mansur (Journal of Industrial Engineering Management, 2022)
In Indonesia, many manufacturing industry companies large and small are trying to make products of good quality to the market. This is because only companies that have good product quality can compete and survive. PT. Fajar Makassar Grafika is a subsidiary of Fajar Group that specifically handles newspaper printing production, in carrying out the process of newspaper production there are still many problems with product defects that are not by the standards of the company.The method used in this study is the Six sigma method using DMAIC stages (define, measure, analyze, improve and control). Six Sigma is one of the tools commonly used in product quality control. This method has the concept of setting quality standards until it reaches 3.4 rejects per one million possibilities.Based on the results of analysis with the Six Sigma method it has been known that in the production process there are 5 types of defects, namely blurred mold defects, dirty prints, not registers, folded and torn newspapers with sigma levels obtained at 3.92 with an average damage rate of 7760 for one million productions (DPMO). From the analysis of fishbone diagrams can be known the causal factors of defective products derived from machine, material and human factors. The proposed improvement is done using Failure Mode and Effect Analysis (FMEA) analysis, so that the company can take precautions and improvements to reduce defective products and improve product quality